Shipbuilding in the United Kingdom in the nineteenth century : a regional approach - Ville, Simon P. (Research in maritime history, 1993)
This volume tackles the history of Shipbuilding in the United Kingdom in the Nineteenth Century by breaking it down into six regions:- Northeast England; Southeast England; Southwest England; Northwest England; Scotland; and Ireland. The intent is to determine the different economic, social, and geographic factors that contribute to the varied rates of rise and decline of Shipbuilding across the United Kingdom, rather than view the nation's shipbuilding history as a singular narrative, which risks omitting the complexity of each region. Each region has been ascribed an author, and each author seeks to establish the quantitative and qualitative nature of output in their region, assessing individual factors of production, the character of the enterprises, and the nature of the market.